Effects of exercise interventions on fatigue of hematopoietic stem cell transplantation patients: A Meta-analysis (运动干预对造血干细胞移植患者疲乏影响的Meta分析) - ZHOU Min (周敏); ZHANG Qing (张清); HU Shaoyan (胡绍燕); ZHOU Xuemei (周雪梅) (中西医结合护理)
Objective To systematically evaluate the effect of exercise interventions on the fatigue for patients with Hematopoietic Stem Cell Transplantation (HSCT) through a meta-analysis. Methods Randomized controlled trials on exercise intervention in patients with HSCT were retrieved from Cochrane library, PubMed, Web of Science, Embase, CINAHL, CNKI, Wanfang Data, VIP, and CBM databases from the establishment to February 2024; ReMan 5. 3 software was used for meta-analysis. Results A total of six studies were included, and the results of meta-analysis showed a statistically significant difference in fatigue scores between the experimental and control groups ［SMD= -0. 24, 95% CI (-0. 44, -0. 03), P<0. 001］; subgroup analysis showed that exercise intervention improved fatigue in HSCT patients ［SMD= -0. 58, 95% CI (-0. 80, -0. 35), P<0. 001］; exercise interventions throughout the transplant period ［SMD= -0. 58, 95% CI (-0. 80, -0. 35), P<0. 001］, and duration longer than 12 weeks ［SMD= -0. 53, 95% CI (-0. 78, -0. 29), P<0. 001］ can reduce fatigue. Conclusion Exercise interventions can effectively improve the fatigue of HSCT patients, and more attention should be paid to exercise intensity, duration and the individualized manner. Studies with high-quality, large-sample, multi-population are needed to further verify its effect. (目的 评价运动干预对造血干细胞移植(HSCT)患者疲乏的影响。方法 检索Cochrane library、PubMed、Web of Science、Embase、CINAHL、中国知网(CNKI)、万方(Wanfang Data)、维普(VIP)、中国生物医学文献数据库(CBM)中HSCT患者运动干预的随机对照试验, 检索时限为建库至2024年2月。采用RevMan 5. 3软件进行Meta分析。结果 共纳入6篇文献, Meta分析结果显示, 试验组与对照组的疲乏得分差异有统计学意义［SMD= -0. 24, 95% CI(-0. 44, -0. 03), P<0. 001］。亚组分析, 运动干预能够改善异基因HSCT患者的疲乏［SMD= -0. 58, 95% CI(-0. 80, -0. 35), P<0. 001］; 贯穿整个移植期［SMD= -0. 58, 95% CI (-0. 80, -0. 35), P<0. 001］、超过12周的运动干预［SMD= -0. 53, 95% CI (-0. 78, -0. 29), P<0. 001］能减轻患者的疲乏。结论 运动干预能够改善HSCT患者的疲乏, 需注意运动的强度、时长及个体化。未来需要高质量、大样本、多人群的研究进一步验证其干预效果。)